2012
DOI: 10.1002/ana.23734
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 12/15‐lipoxygenase as therapeutic strategy to treat stroke

Abstract: Targeting newly identified damage pathways in the ischemic brain can help to circumvent the currently severe limitations of acute stroke therapy. Here we show that the activity of 12/15-lipoxygenase was increased in the ischemic mouse brain, and 12/15-lipoxygenase co-localized with a marker for oxidized lipids MDA2. This co-localization was also detected in the brain of two human stroke patients, where it also coincided with increased apoptosis-inducing factor, AIF. A novel inhibitor of 12/15-lipoxygenase, LOX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
126
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(134 citation statements)
references
References 34 publications
7
126
0
Order By: Relevance
“…As a measure of STAT activity in the brain after ischemia, we used antibodies to detect p-STAT1 and p-STAT6 in brain sections of a 77-year-old female patient with ischemic stroke. 3 Western blotting showed increased levels of p-STAT1 and p-STAT6, respectively, in the sample from the peri-infarct region compared with contralateral cortex ( Figure 6A). These findings, which reflect increased activity of both of these transcriptional activators, were confirmed by immunohistochemistry ( Figure 6B).…”
Section: Increased Levels Of Activated P-stat1 and P-stat6 In Human Smentioning
confidence: 99%
See 3 more Smart Citations
“…As a measure of STAT activity in the brain after ischemia, we used antibodies to detect p-STAT1 and p-STAT6 in brain sections of a 77-year-old female patient with ischemic stroke. 3 Western blotting showed increased levels of p-STAT1 and p-STAT6, respectively, in the sample from the peri-infarct region compared with contralateral cortex ( Figure 6A). These findings, which reflect increased activity of both of these transcriptional activators, were confirmed by immunohistochemistry ( Figure 6B).…”
Section: Increased Levels Of Activated P-stat1 and P-stat6 In Human Smentioning
confidence: 99%
“…From previous studies in mice and humans, we know that 12/15-LOX is increased in the peri-infarct region as well, coincident with the AIF. [3][4][5][6] To determine a possible link to the disease state of the corresponding cells, we performed colocalization studies with sections taken from the peri-infarct cortex. Double labeling with the corresponding antibodies showed that p-STAT6 and p-STAT1 are increased in the same cells; p-STAT6 colocalizes with the oxidative stress marker MDA2, and with AIF; the same cells that show increased AIF also show high levels of 12/15-LOX; and the 12/15-LOXpositive cells are also positive for p-STAT1 ( Figure 6C, top to bottom).…”
Section: Increased Levels Of Activated P-stat1 and P-stat6 In Human Smentioning
confidence: 99%
See 2 more Smart Citations
“…1) Emerging data suggest that LOXs play essential roles in the pathogenesis of various neurological diseases. [7][8][9][10][11] For instance, the expression and activity of 12,15-LOX are upregulated in the brain following cerebral ischemia. 7) Consequently, 12,15-LOX inhibitors ameliorate brain infarct damage via direct neuroprotection against oxidative stress.…”
mentioning
confidence: 99%